2014
DOI: 10.1186/bf03353035
|View full text |Cite
|
Sign up to set email alerts
|

A simple method for deriving the uniform field MT responses in auroral zones

Abstract: Source field effects in magnetotelluric data acquired at high geomagnetic latitudes can result in erroneous interpretations of Earth conductivity structure deep within the mantle. This paper describes a simple technique most appropriate for a region that is dominantly one-dimensional (1-D) and uses the vertical magnetic field variations for identifying intervals of likely low contamination by non-uniform sources. Times are chosen when the variations stay within prescribed limits defined on the basis of a histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 35 publications
1
33
2
Order By: Relevance
“…Corridor 1 is located at a relatively high geomagnetic latitude (66°N-69°N), and the recorded MT time series contains relatively strong geomagnetic activity, particular around local midnight, interpreted to be associated with the auroral electrojet. The nonuniform source field associated with these signals can cause appreciable bias to the MT response at periods longer than a few tens of seconds (Jones 1980;Garcia et al 1997;Jones and Spratt 2002). The 2 × 2 complex MT impedance tensor, which relates the horizontal electric and magnetic fields, is the fundamental response determined from the recorded electric and magnetic field components (e.g., Vozoff 1991).…”
Section: Magnetotelluric Survey and Data Processingmentioning
confidence: 99%
“…Corridor 1 is located at a relatively high geomagnetic latitude (66°N-69°N), and the recorded MT time series contains relatively strong geomagnetic activity, particular around local midnight, interpreted to be associated with the auroral electrojet. The nonuniform source field associated with these signals can cause appreciable bias to the MT response at periods longer than a few tens of seconds (Jones 1980;Garcia et al 1997;Jones and Spratt 2002). The 2 × 2 complex MT impedance tensor, which relates the horizontal electric and magnetic fields, is the fundamental response determined from the recorded electric and magnetic field components (e.g., Vozoff 1991).…”
Section: Magnetotelluric Survey and Data Processingmentioning
confidence: 99%
“…thesis: Stevens (1999 B.Sc. theses: Cassels (1997); Norton (2000); Gowan (2005) Jones and Ferguson (2001a); Jones et al (2001c); Jones and Spratt (2002); Ledo et al (2002); Wu et al (2002); Eaton et al (2004b); Ledo et al (2004a); Ledo and Jones (2005); Wu et al (2005); Lezaeta et al (2007); Moorkamp et al (2007); Spratt et al (2009); Moorkamp et al (2010) Ph.D. thesis: Wu (2001) M.Sc. thesis: Wennberg (2003) B.Sc.…”
Section: The Canadian Mt Databasementioning
confidence: 96%
“…Garcia et al (1997) examined the effect of non-uniform fields associated with high auroral activity on local night-time recordings from MT data recorded on the northernmost Lithoprobe THOT, and showed that a robust controlled-leverage processing algorithm could extract stable uniform field estimates of the MT impedance tensor. Source field effects were most acute on the Slave part of the SNORCLE transect, and methods for dealing with nonuniform sources fields were advanced by Jones and Spratt (2002) and Lezaeta et al (2007). The former used the property that the vertical magnetic field tipper response is far more sensitive to non-uniform fields than is the MT response, whereas the latter approach was more mathematical in nature using a frequency domain principal component method.…”
Section: Mt Technique Developmentmentioning
confidence: 99%
“…2, in comparison with the effect on impedance data, the effect on the vertical magnetic field TFs (tippers) generally appears to be more significant. This is perhaps to be expected, as tippers are more dependent on source characteristics than impedances (e.g., Jones and Spratt 2002). Biases in the tippers may sometimes be large enough that these data should be excluded from an inversion.…”
Section: Implications For Mt Data Inversionsmentioning
confidence: 97%
“…In the FLR period band for this array (~ 20-40 s), the curve for the third mode becomes significant. Additional significant modes at longer periods are also associated with source effects (primarily in the vertical magnetic fields) due to increasing skin depths with respect to large-scale source structure (e.g., Jones and Spratt 2002). b-d Linear combinations of the first three spatial modes at a period of 26 s, displayed as complex vectors plotted on a map of array sites.…”
Section: Pc's and The 3d Earthmentioning
confidence: 99%